The Federal Government and Tripartism - Adams, Roy (Relations industrielles / Industrial Relations, 1982)
Some of the most highly developed tripartite Systems have been established in the Scandinavian countries, in Holland and in Belgium. The difficulties in implementing such a System in Canada are examined.